Ultraviolet Radiation-Induced Tolerogenic Dendritic Cells in Skin: Insights and Mechanisms - Gelare Ghajar-Rahimi; Nabiha Yusuf; Hui Xu (Cells, 2025)
Ultraviolet (UV) radiation has profound effects on the immune system, including the induction of tolerogenic dendritic cells (DCs), which contribute to immune suppression and tolerance. This review explores the roles of conventional CD11c⁺ DCs, as well as cutaneous Langerhans cells and CD11b⁺ myeloid cells, in UV-induced immune modulation. Two key mechanisms underlying the immunosuppressive relationship between UV and DCs are discussed: the inactivation of DCs and the induction of tolerogenic DCs. DCs serve as a critical link between the innate and adaptive immune systems, serving as professional antigen-presenting cells. In this context, we explore how UV-induced DCs influence the activity of specific T cell subsets, including regulatory T lymphocytes and T helper cells, and shape immune outcomes. Finally, we highlight the implications of UV-induced tolerogenic DCs in select dermatologic pathologies, including cutaneous lupus, polymorphic light eruption, and skin cancer. Understanding the mechanisms by which UV radiation alters DC function offers insights into the complex interplay between environmental factors and immune regulation, providing potential avenues for preventive and therapeutic intervention in UV-induced skin diseases.